The lifestyle influence on alcoholic pancreatitis versus alcoholic liver disease: a case-control study - Canha, Maria Inês Silvestre Rêgo (2017)
Trabalho de Projeto do Mestrado Integrado em Medicina apresentado à Faculdade de Medicina